Optimalisasi Media Digital untuk Penguatan Literasi Digital dan Entrepreneurial Mindset Siswa SMA Unggulan Amanatul Ummah Surabaya - Dwi Novitasari; Dina Anggraeni Susesti; Endah Tri Wahyuningtyas; Dhini Yuliana Siska; Arinda Tri Apriliyah (Kilau Publishing, 2026)
This community service activity aims to improve the understanding of students at SMA Unggulan Amanatul Ummah Surabaya regarding digital literacy and digital media-based entrepreneurship. The methods used include socialization, training, practice, and evaluation through pre-tests and post-tests. The results showed an increase in participants' understanding, marked by an increase in scores on several indicators from 91.7–95.8% to 96–100%, while other indicators remained at the maximum score. This activity effectively enhances students' digital literacy competencies and entrepreneurial mindset and is feasible to be applied sustainably in the school.